1989
DOI: 10.1007/bf00858537
|View full text |Cite
|
Sign up to set email alerts
|

The immune status of uraemic children/adolescents with chronic renal failure and renal replacement therapy

Abstract: In adults with chronic renal failure (CRF) and/or renal replacement therapy (RRT) various immunological abnormalities have been described, but few data are available for the paediatric age group. We performed basic in vitro immunological studies in 26 patients 10 months-19 years of age with advanced renal failure, 11 with CRF (creatinine clearance 16.8 +/- 5.2 ml/min per 1.73 m2), 15 on RRT with haemodialysis (HD; n = 9) and continuous ambulatory peritoneal dialysis (CAPD; n = 6) as well as in 16 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 9 publications
2
7
0
1
Order By: Relevance
“…The results of the present study together with those of others reported so far [6, 7, 8, 9, 10, 11, 12, 14]suggest that children with CRF are not immunocompromised, though the effects of uraemia may change various components of their immune system.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The results of the present study together with those of others reported so far [6, 7, 8, 9, 10, 11, 12, 14]suggest that children with CRF are not immunocompromised, though the effects of uraemia may change various components of their immune system.…”
Section: Discussionsupporting
confidence: 63%
“…According to these studies, adults with chronic renal failure (CRF) showed an impaired immune status and a poor immunological response to vaccination [1, 2, 3, 4, 5]. However, in uraemic children, these findings appear to be different from those of adults [2, 6, 7, 8, 9, 10, 11, 12]. …”
Section: Introductionmentioning
confidence: 93%
“…Children with CRF have -in contrast to adult patientsno significant immune impairment, except in a few clinical conditions (e.g., nephrotic syndrome, systemic lupus erythematosus). Reduced serum immunoglobulin concentrations have been found in children on peritoneal dialysis (PD) [8,9,10,11]. Standard vaccination schedules generally induce an antibody response in children with CRF [12,13,14,15,16,17], although specific revaccination is recommended [17].…”
Section: Introductionmentioning
confidence: 99%
“…Successful renal transplantation markedly improves the quality of life for children with end-stage renal disease [14], However, despite recent advances in immunosup pressive therapy, renal transplantation in children is not as successful as in adults [15,16], This may be explained by problems of surgical technique, a greater incidence of graft thrombosis in children, variable CS-A metabolism, preferential allocation of organs from pediatric donors to pediatric recipients, and a state of heightened immuno logic responsiveness in children relative to adults [17][18][19][20]. In addition, childhood viral infections such as varicella [21] and CMV may further increase the difficulties of pediatric renal transplantation.…”
Section: Discussionmentioning
confidence: 99%